Kaempferol Protects Against Cerebral Ischemia Reperfusion Injury Through Intervening Oxidative and Inflammatory Stress Induced Apoptosis - Wang, Jing; Mao, Junqin; Wang, Rong; Li, Shengnan; Wu, Bin; Yuan, Yongfang (Frontiers in Pharmacology, 2020)
The aim of this research is to investigate the potential neuro-protective effect of kaempferol which with anti-oxidant, anti-inflammatory and immune modulatory properties, and understand the effect of kaempferol on reducing cerebral ischemia reperfusion injury in vivo. Male adult Sprague Dawley rats were pretreated with kaempferol for one week via gavage before cerebral ischemia reperfusion(I/R) injury operation. We found that kaempferol treatment can reduce the cerebral infarct volume and neurological score after cerebral I/R. Rats were sacrificed after 24 hours reperfusion. We observed that kaempferol improved the arrangement, distribution and morphological structure of neurons, as well as attenuated cell apoptosis in brain tissue via H&E staining, Nissl staining and TUNEL staining. SOD, MDA and GSH kit analysis, ELISA assay, Real-time PCR, Western blot, and immunohistochemical examination indicated that kaempferol mitigated oxidative and inflammatory stress via regulating the expression of proteins, p-Akt, p-GSK-3β, Nrf-2 and p-NF-κB during cerebral I/R, thus increasing the activity of SOD and GSH, meanwhile decreasing the content of MDA in serum and brain tissue, as well as restoring the expression levels of TNF-α, IL-1β and IL-6 in vivo. Taken together, this study suggested that kaempferol protects against cerebral ischemia reperfusion induced brain damage. The possible mechanism is related with inhibiting oxidative and inflammatory stress induced apoptosis.